Pengaruh Media Loose Part Dalam Mengembangkan Kemampuan Mengenal Huruf Anak Usia Dini 5–6 Tahun di Taman Kanak-Kanak Yayasan Amalan Kota Padang - Laura; Indra Yeni; Rakimahwati; Elise Muryanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to determine the effect of loose parts media on developing letter recognition skills among children aged 5–6 years at Yayasan Amalan Kindergarten, Padang. Letter recognition is a fundamental aspect of early childhood language development that supports later reading and writing skills. This research employed a quantitative approach using a quasi-experimental method with a Pre-test–Posttest Control Group Design. The participants consisted of an experimental group receiving instruction through loose parts media and a control group receiving conventional learning activities. Data were collected through observation using a letter recognition assessment instrument. Data analysis included normality tests, homogeneity tests, and independent sample t-tests. The findings revealed that children in the experimental group showed greater improvement in letter recognition skills than those in the control group. The use of loose parts media encouraged children to actively explore, manipulate, and create learning experiences through play, making the learning process more engaging, enjoyable, and meaningful. Therefore, loose parts media had a positive and significant effect on improving letter recognition skills in children aged 5–6 years